Links Between Leader Identity, Leadership Identity and Their Fusion - Raudonė, Odeta (Vilnius University Proceedings, 2023)
Growing body of research in leader and leadership identity exhibits the topic’s importance in today’s turbulent and uncertain global environment. Leader identity, which is related to the personal development of the leader, analysed at personal, relational and collective (group) levels. However, leader identity does not fully support leadership. Leaders operate and grow within the context of the people they lead – the group, the followers, who collectively possess social (group) identity. Researchers view this as a complex phenomenon involving shared values, perspectives and goals. There is no distinct line that separates leader identity from group identity, but there is an area where they clash. As a personevolves as a leader, leader identity is expected to incorporate more elements of group identity and develop towards it, although that is not inevitable. The current studyemphasises leader-follower interactions and identity fusion, linking them to identity leadership development and suggesting possible outcomes
Keywords: leader identity; leader-follower interactions; identity fusion; identity leadership